2021
DOI: 10.1002/pi.6342
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic modified poly(l‐glutamic acid) graft copolymer micelles with ultrahigh drug loading capacity for anticancer drug delivery

Abstract: Self‐assembled polymeric nanoparticle (NP) drug carriers are capable of encapsulated and controlled delivery, facilitating improvements in the therapeutic efficiency of drugs. Here we report a series of poly(l‐glutamic acid)‐g‐methoxy poly(ethylene glycol)/4‐phenylbutyl ester (PLG‐g‐mPEG/PB) copolymers, which were synthesized by esterification of 4‐phenylbutanol (PB) and PLG‐g‐mPEG in different feed ratios. The copolymers obtained form into nano‐sized micelles in aqueous solution by a self‐assembly process, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…An alternative way to obtain polypeptides bearing the functional moieties of interest is the post-polymerization modification of a poly(amino acid) main chain [ 12 ]. In the case of poly(amino acids), this approach is mainly used to modify them with thermo-responsive moieties [ 12 ], PEG [ 12 ], sugars [ 8 , 13 ] and hydrophobic molecules [ 14 , 15 ]. In particular, Xue et al reported the modification of poly(L-ornithine- co -L-citrulline) with N-succinimidyl N-methylcarbamate to obtain thermo-responsive copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative way to obtain polypeptides bearing the functional moieties of interest is the post-polymerization modification of a poly(amino acid) main chain [ 12 ]. In the case of poly(amino acids), this approach is mainly used to modify them with thermo-responsive moieties [ 12 ], PEG [ 12 ], sugars [ 8 , 13 ] and hydrophobic molecules [ 14 , 15 ]. In particular, Xue et al reported the modification of poly(L-ornithine- co -L-citrulline) with N-succinimidyl N-methylcarbamate to obtain thermo-responsive copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Amidation and azide-alkyne cycloaddition are among the most popular modification techniques [ 8 , 21 ]. In the case of hydrophobization, the modifications of poly(glutamic acid) with 4-phenylbutanol [ 15 ], p -aminoazobenzene [ 22 ], Boc-protected α,ω-aminoalcohols containing different alkyl spacers [ 23 ], cinnamyl alcohol [ 24 ] and coumarin derivative [ 25 ] are reported. The modification of poly(L-lysine) with L-histidine is one of the most popular approaches to obtaining polypeptides sensitive to physiological pH values [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These nanoaggregates are capable of encapsulating the hydrophobic dye NR inside their hydrophobic core, thus demonstrating their hydrophobic drug loading capability. 51 The copolymers with alanine and dehydroabietate pendents are expected to be biocompatible, as these are amino acid and natural product, respectively. 52 Currently, we are widening our research with other amino acid based copolymers having dehydroabietate pendents to achieve substantial efficacy of drug loading and controlled release of encapsulated drug at different pH values.…”
Section: Discussionmentioning
confidence: 99%
“…Various weaker interactions were employed in polymer self‐assembly systems, resulting in diverse/hierarchical nanomaterials 7–11 . In particular, the nanoassembles formed by synthetic biomacromolecules and amphiphilic copolymers are promising candidates in bio‐related applications 12–15 . Moreover, combining experiments and simulations to study the self‐assembly mechanism can advance mechanistic research in this field, 2,11 which is one of the vital development directions.…”
mentioning
confidence: 99%
“…prepared polymeric micelles from poly(L‐glutamic acid) graft copolymer system, the drug loading content and the loading efficiency can reach an ultrahigh value of 28.2 wt% and 94%, respectively. This self‐assembly system can provide a promising carrier for hydrophobic anticancer drug delivery 13 . Jiang et al .…”
mentioning
confidence: 99%